Using critical analysis to develop metacognitive ability and critical thinking skills in biology - Marheny Lukitasari; Rusdi Hasan; Wasilatul Murtafiah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Possessing and developing metacognitive abilities are an essential part of the learning process. This study is a class action research on the use of critical analysis to identify its influence on students’ metacognitive abilities and critical thinking skills as well as to discover the relationship between metacognitive abilities and critical thinking skills. The sample of this study is 76 students from 217 students taking cell biology and non-vascular plants subject during the fall semester. It is a descriptive quantitative study with critical analysis assignments. Critical analysis rubric is used to collect the data of students’ critical analysis and the essay test to measure students’ critical thinking and metacognitive ability. The data of metacognitive ability and critical thinking were analyzed using regression test. The result showed there was a positive influence of the use of critical analysis to the student metacognitive abilities and critical thinking skills. The results of a simple correlation analysis of metacognitive abilities and critical thinking skills show the means value (r) of 0.904, which means that there is a strong positive relationship between the two components. The higher the student’ metacognitive skills, the higher their critical thinking skill will be.